2005
DOI: 10.1017/s1461145705005699
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal grey-matter changes in short-term and long-term abstinent methamphetamine abusers

Abstract: Authors explored grey-matter density in 29 methamphetamine abusers and 20 healthy comparison subjects using voxel-based morphometry. Grey-matter density changes and performances on the Wisconsin Card Sorting test (WCST) were also compared between 11 short-term (<6 months) and 18 longterm (o6 months) abstinent methamphetamine abusers. Methamphetamine abusers had lower greymatter density in the right middle frontal cortex (corrected p<0.05) and more total errors in the WCST (p<0.01) relative to healthy compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
130
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(147 citation statements)
references
References 25 publications
13
130
4
Order By: Relevance
“…In MA-dependent humans, MA intake typically ranges between 0.5 to 1.4 g per day (Hoffman et al, 2006;Kim et al, 2006;King et al, 2010;Simon et al, 2002), with daily intake most likely being restricted by the financial cost of MA and/ or the physiological/psychological consequences of use (eg, hyperactivity, psychosis). Assuming that an average adult weighs B80 kg (Ogden et al, 2004), this equates to an intake of 6-17.5 mg/kg per day, although purity of the source and method of administration can affect the precise amount of MA ingested.…”
Section: Animals Exposed To Ma Will Show Cognitive Decline Particulamentioning
confidence: 99%
See 2 more Smart Citations
“…In MA-dependent humans, MA intake typically ranges between 0.5 to 1.4 g per day (Hoffman et al, 2006;Kim et al, 2006;King et al, 2010;Simon et al, 2002), with daily intake most likely being restricted by the financial cost of MA and/ or the physiological/psychological consequences of use (eg, hyperactivity, psychosis). Assuming that an average adult weighs B80 kg (Ogden et al, 2004), this equates to an intake of 6-17.5 mg/kg per day, although purity of the source and method of administration can affect the precise amount of MA ingested.…”
Section: Animals Exposed To Ma Will Show Cognitive Decline Particulamentioning
confidence: 99%
“…Of these eight studies (see Table 1), five found that the MA-dependent participants performed worse than the control participants on a subset of the cognitive tests administered (Hoffman et al, 2006;Kim et al, 2006;Rippeth et al, 2004;Salo et al, 2007Salo et al, , 2009. The other three studies did not find significant differences between the groups on multiple cognitive tests (Chang et al, 2005;King et al, 2010;Simon et al, 2010), although two of these studies used Bonferroni correction for statistical significance, and this method may be overly conservative when dependent variables are interrcorrelated (Miller, 1981), as is the case with performance on most cognitive tests (Warner et al, 1987).…”
Section: Individuals Who Abuse Ma Will Have Worse Cognitive Performanmentioning
confidence: 99%
See 1 more Smart Citation
“…1,31 Excessive exposure to methamphetamine has also has been linked to chronic health risks such as coronary heart disease, cardiomyopathy, pulmonary edema, stroke, and seizures. 31,32,33 Other effects of methamphetamine use include, dermatological infections, skin ulcerations,…”
Section: Biopsychosocial/ Neurological Effectsmentioning
confidence: 99%
“…The main functions altered are learning, episodic memory, executive functions, speed of information treatment, working memory and perceptual narrowing [63]. The cognitive deficits persist over six months after withdrawal [64,65].…”
Section: Neuropschological Impairmentmentioning
confidence: 99%